Teratogenic and toxic effects of Lingzhi or Reishi medicinal mushroom, Ganoderma lucidum (W.Curt.:Fr.) P. Karst. (Higher basidiomycetes), on zebrafish embryo as model - Dulay, Rich Milton R. (Animo Repository, 2012)
This paper highlights the teratogenic and toxic effects of Ganoderma lucidum (Lingzhi or Reishi mushroom) extract on zebrafish embryos. Hatchability, malformations, and lethality rate of zebrafish embryos were assessed to provide valuable information regarding the potential teratogenic activity of G. lucidum. Hatching was completed 48 h post treatment application (hpta) at 1% or lower concentrations of extract and embryo water. The hatching rate of embryos treated with 5% or higher concentrations was significantly lower (p > 0.05) than the control. Tail malformation was the most marked morphological abnormality in embryos at 72 hpta, which was obviously caused by 1% extract (55.56% tail malformation) and was observed in all embryos exposed to 5% of extract. Growth retardation was evident in embryos exposed to 5%, 10%, and 20%. However, lethal effect of extract of G. lucidum was dependent on dose and time of exposure. Mortality rates of embryos treated with 5% (44.44%) or higher concentrations of the extract was significantly higher (p < 0.05) than that of the control embryos at 72 hpta. These results suggest that G. lucidum extract has lethal and sub-lethal effects on zebrafish embryos. © 2012 Begell House, Inc.